AB1170 A PHASE IV, MULTICENTER, SINGLE-ARM, OPEN-LABEL STUDY TO EVALUATE THE IMPACT OF APREMILAST ON HAND AND WHOLE-BODY MRI OUTCOMES IN PATIENTS WITH PSORIATIC ARTHRITIS (MOSAIC): RATIONALE, DESIGN AND METHODS. (June 2019) - Ǿstergaard, Mikkel; Maksymowych, Walter P.; Boesen, Mikael; Kubassova, Olga; Nakasato, Priscila; Guerette, Benoit; Teng, Lichen; Mease, Philip J.
Abstract : Background: Phase III clinical trials have shown apremilast (APR) reduced PsA signs/symptoms and improved physical function, 1-3 but no study has addressed its impact on structural disease progression. MRI is a highly sensitive, validated tool to assess inflammatory and structural changes, as it can detect soft tissue inflammation, bone marrow edema (BME) lesions, bone erosion and proliferation in peripheral joints and axial skeleton. Whole-body (WB)-MRI, a relatively novel technique in musculoskeletal studies, allows assessment of all peripheral/axial joints and entheses in 1 examination. 4 Recent, consensus-based and semi-quantitative scoring methods were developed and validated. This study is the first to systematically use new state-of-the-art MRI scoring methodologies to assess PsA inflammatory and structural changes in a global clinical trial. Objectives: To assess APR efficacy on inflammatory indices and imaging outcome measures associated with PsA structural progression by conventional static MRI and dynamic contrast-enhanced (DCE)-MRI of the most affected hand and WB-MRI. Methods: The study aims to enroll 120 biologic-naïve adults with PsA for ≥3 mos to ≤5 yrs and prior treatment with ≤2 conventional DMARDs. Subjects must have ≥3 swollen and ≥3 tender joints, hand involvement (≥1 swollen joint or ≥1 dactylitis) and ≥1 active enthesitis site. After 4-wk screening, all eligible patients will receive APR 30 mg twice daily (titrated during the first 5 days) as monotherapy or in combination with methotrexate for 48 wks, with a 4-wk observational follow-up. Conventional MRI and optional DCE-MRI of the most affected hand and WB-MRI of the entire body will be performed at Wks 0, 24 and 48. The primary endpoint is change from BL to Wk 24 in OMERACT PsA MRI (PsAMRIS) composite score of BME + synovitis + tenosynovitis. Other imaging endpoints include change from BL to Wk 48 in PsAMRIS composite score (BME + synovitis + tenosynovitis) and change from BL to Wks 24 and 48 in PsAMRIS composite score (BME + synovitis), PsAMRIS composite inflammation score (BME + synovitis + tenosynovitis + periarticular inflammation), PsAMRIS total damage score (erosion + bone proliferation), WB-MRI indices (including peripheral joint inflammation index and peripheral enthesis inflammation index), hip and knee inflammation MRI scores (HIMRISS, KIMRISS), OMERACT heel enthesitis MRI indices, axial inflammation indices (SPARCC, CanDen), DEMRIQ-Volume and DEMRIQ-Inflammation and other DCE-MRI–derived parameters. Clinical parameters will include SJC/TJC, cDAPSA, SPARCC Enthesitis Index, Leeds Enthesitis Index, Leeds Dactylitis Index, PASDAS, PtGA, PhGA, Patient's Assessment of Pain, HAQ-DI, and BASDAI and impact of disease (PsAID12). Safety and tolerability also will be assessed. Results: The study protocol was approved by an independent ethics committee and is now enrolling in the USA. Selected countries in Europe and Russia will also participate. MRI, clinical and patient-reported outcomes will be analyzed. Conclusion: This study will provide important evidence of APR's impact on inflammatory/structural changes by assessing all PsA musculoskeletal domains (peripheral arthritis, enthesitis, dactylitis and axial disease). Furthermore, it will yield information on use of conventional MRI–, WB-MRI– and DCE-MRI–driven outcome measures in PsA clinical trials. References: [1] Kavanaugh 2014. 2. Cutolo 2016. 3. Edwards 2016. 4. Østergaard 2017. Disclosure of Interests: Mikkel Ǿstergaard Grant/research support from: Abbvie, Celgene, Centocor, Merck, Novartis, Consultant for: Abbvie, BMS, Boehringer-Ingelheim, Celgene, Eli Lilly, Hospira, Janssen, Merck, Novartis, Novo, Orion, Pfizer, Regeneron, Roche, and UCB, Speakers bureau: Abbvie, BMS, Boehringer-Ingelheim, Celgene, Eli Lilly, Hospira, Janssen, Merck, Novartis, Novo, Orion, Pfizer, Regeneron, Roche, and UCB, Walter P Maksymowych Grant/research support from: AbbVie, Pfizer, Janssen, Novartis, Consultant for: AbbVie, Eli Lilly, Boehringer, Galapagos, Janssen, Novartis, Pfizer and UCB Pharma; Chief Medical Officer for Canadian Research and Education Arthritis, Mikael Boesen Shareholder of: Image Analysis Group, UK, Grant/research support from: Image Analysis Group, UK, OAK Foundation, EUROSTAR, Consultant for: Esaote, Eli Lilly, Celgene, Carestream, UCB, Abbvie, Pfizer, Astra Zeneka, Roche, Siemens, Image Analysis Group, Olga Kubassova Shareholder of: IAG, Image Analysis Group, Employee of: IAG, Image Analysis Group, Priscila Nakasato Employee of: Celgene Corporation, Benoit Guerette Employee of: Celgene Corporation, Lichen Teng Employee of: Celgene Corporation, Philip J Mease Grant/research support from: AbbVie, Amgen, BMS, Celgene, Janssen, Lilly, Novartis, Pfizer, SUN and UCB, Consultant for: AbbVie, Amgen, BMS, Galapagos, Gilead Sciences, Inc., Janssen, Lilly, Novartis, Pfizer, SUN and UCB, Speakers bureau: AbbVie, Amgen, BMS, Celgene, Genentech, Janssen, Lilly, Novartis, Pfizer and UCB